The Effect of Young Coconut Water (Cocos Nucifera L.) Consumption on VO2max in Young Adults Non-Athletes - Aris Prasetyo; Dheis Aninditha Suspim (Faculty of Medicine, University of Jember, 2021)
Abstract The availability of carbohydrates and electrolytes in the body greatly affects Volume Oxigen Maximum (VO2max) to maintain stamina and endurance. The administration of young coconut water has the effect of increasing VO2max because it contains carbohydrates and electrolytes. The administration of young coconut water 15-60 minutes before exercise has the potential to delay exhaustion and increasing performance because glucose levels are maintained and muscle glycogen stores are restored. The purpose of this study was to determine the effect of administration of young coconut water on VO2max in young adults non-athletes. This study used a quasi experimental research design with a cross over design clinical trial. A total of 30 male non-athletes aged 18-24 years who fulfill the inclusion criteria were divided into groups randomLy, the treatment group (given 300 mL of coconut water) and the control group (given 300 mL of mineral water) 60 minutes before treatment, then crossover carried out 3 days after treatment. The results showed the control group fitness index was 141.83 ± 44.69, and the fitness index of the treatment group was 176.01 ± 59.07. The sample characteristics based on VO2max showed that the treatment group had a greater VO2max by a mean of 4.84 ± 1.05 compared to the control group with a mean of 4.19 ± 0.78. The results of the Paired T-Test showed a significance value of p= 0.000 (p <0.05) indicating that there was a significant difference between the control group and the treatment group. The conclusion of this study is that giving young coconut water increases VO2max levels in young adults non-athletes. Keywords: Young coconut water, VO2max, fitness index